Metabolic syndrome in Spanish patients with psoriasis needing systemic therapy: Prevalence and association with cardiovascular disease in PSO-RISK, a cross-sectional study. (August 2015) - Belinchón, I.; Vanaclocha, F.; de la Cueva-Dobao, P.; Coto-Segura, P.; Labandeira, J.; Herranz, P.; Taberner, R.; Juliá, B.; Cea-Calvo, L.; Puig, L.
Abstract Background: Increasing evidence indicates a relationship between psoriasis and metabolic syndrome (MS). We evaluated the prevalence of MS in patients receiving systemic treatment for psoriasis in Spain, and its relationship to cardiovascular disease (CVD). Methods: This cross-sectional, multicenter, non-interventional study enrolled 368 patients with moderate-to-severe psoriasis requiring systemic treatment. Clinical parameters for psoriasis, CV risk factors, MS and CVD were assessed. Descriptive and logistic regression analyses were performed. Results: 352 patients were included (median psoriasis duration: 18 years, plaque psoriasis [95.7%], psoriatic arthritis [22.8%]). Overall, 132 patients (37.5%) fulfilled diagnostic criteria for MS; the most prevalent MS components were high blood pressure and increased waist circumference. Patients with MS were older, more likely to be obese and to have a sedentary lifestyle and hypercholesterolemia than those without MS. CVD was more prevalent in patients with MS than in those without (29.5% versus 15.9%, p = 0.002), particularly coronary heart disease (CHD), myocardial infarction and heart failure. MS was independently associated with CVD (OR 1.98, p = 0.018) and CHD (OR 2.02, p = 0.044). Conclusion: The prevalence of MS was high among patients with moderate-to-severe psoriasis requiring systemic treatment, and was associated with a higher prevalence of CVD. Dermatologists should consider implementing simple screening protocols.